Implikasi Idiosinkratik Barack Obama terhadap Kebijakan Kerjasama Kontraterorisme Amerika-Arab Saudi - Nandareska, Ikko Vidia; Windiani, Reni (Journal of International Relations, 2018)
This research aims to find out the leader personality of Barack Obama and it isimplications to U.S-Saudi Arabia counterterrorism cooperation trough the MargaretHermannâ€™s leader personality typology (1980). U.S counterterrorism under Bushâ€™spresidency often use hard power. Bush rhetoric shows strong dichotomy as â€œgood Vs evilâ€.There are differences in foreign policy approaches during the bush and Obama. U.S underBarack Obamaâ€™s presidency not as dominance as in the Bush era and no longer used hardpower. U.S has counterterrorism cooperation with Saudi Arabia that has been linked toterrorism ever since 9/11. This research sees Obamaâ€™s background and life experiences,U.S-Saudiâ€™s counterterrorism cooperation and terrorism threat for U.S post 9/11. Usingqualitative method with secondary and primary data source, the result of this researchshows that Barack Obamaâ€™s background and life experiences influence his views andpolicy orientation. Obama has the personality of conciliatory leader that consist of fiveindicators: low nationalism, low distrust to others, high need for affiliation, highconceptual complexity and little believe in own control. His conciliatory personality isimplies in the approach of U.S counterterrorism efforts with Saudi Arabia. U.S becomemore tolerant and rely on Saudi Arabia's role in the region to counter terrorism.